The anti-apoptotic protein HAX-1 interacts with SERCA2 and regulates its protein levels to promote cell survival - Vafiadaki, E.; Arvanitis, DA; Pagakis, S. N.; Papalouka, V.; Sanoudou, D.; Kontrogianni-Konstantopoulos, A.; Kranias, EG (Mol Biol CellMol Biol CellMol Biol Cell, 2009)
Cardiac contractility is regulated through the activity of various key Ca(2+)-handling proteins. The sarco(endo)plasmic reticulum (SR) Ca(2+) transport ATPase (SERCA2a) and its inhibitor phospholamban (PLN) control the uptake of Ca(2+) by SR membranes during relaxation. Recently, the antiapoptotic HS-1-associated protein X-1 (HAX-1) was identified as a binding partner of PLN, and this interaction was postulated to regulate cell apoptosis. In the current study, we determined that HAX-1 can also bind to SERCA2. Deletion mapping analysis demonstrated that amino acid residues 575-594 of SERCA2's nucleotide binding domain are required for its interaction with the C-terminal domain of HAX-1, containing amino acids 203-245. In transiently cotransfected human embryonic kidney 293 cells, recombinant SERCA2 was specifically targeted to the ER, whereas HAX-1 selectively concentrated at mitochondria. On triple transfections with PLN, however, HAX-1 massively translocated to the ER membranes, where it codistributed with PLN and SERCA2. Overexpression of SERCA2 abrogated the protective effects of HAX-1 on cell survival, after hypoxia/reoxygenation or thapsigargin treatment. Importantly, HAX-1 overexpression was associated with down-regulation of SERCA2 expression levels, resulting in significant reduction of apparent ER Ca(2+) levels. These findings suggest that HAX-1 may promote cell survival through modulation of SERCA2 protein levels and thus ER Ca(2+) stores.
Keywords: *Cell Survival; Adaptor Proteins, Signal Transducing; Animals; Calcium-Binding Proteins/genetics/metabolism; Calcium/metabolism; Cell Line; Endoplasmic Reticulum/metabolism; Enzyme Inhibitors/metabolism; Humans; Hydrogen Peroxide/metabolism; Mice; Mice, Knockout; Oxidants/metabolism; Protein Binding; Protein Interaction Mapping; Proteins/genetics/*metabolism; Sarcoplasmic Reticulum Calcium-Transporting ATPases/genetics/*metabolism; Thapsigargin/metabolism